Networks of Talent Support in Hungary - Bencéné Fekete, Andrea (Acta Scientiarum Socialium, 2015)
Networks of Talent Support in Hungary In talented people there is intellectual capital; the future of humanity and the societies depends on the education of young people and the support of talents. In the past decades a unique system of talent support was established in Hungary which provides an opportunity for all talented individuals regardless of social status to deploy their talents. An inter- and intraregional network of talent support system has been created which may even cross the borders of our country. The aim of the talent support activity is not only the development of outstanding performance, but also to raise happy, confident individuals. And the keys to success are well-educated, enthusiastic pedagogues and a supportive family background.
Keywords: network; talent support; education; Hungary